Teaching on the Move. Social Education Toolkit for Teachers - Bazuń, Dorota - ed.; Kwiatkowski, Mariusz - ed. (Warszawa: Oficyna Naukowa)
We are aware that education on the move can be introduced where teachers are convinced that it is worth working with students in this way. We are working on the "Teaching on the Move. Social Education Toolkit for Teachers", which will show the possibilities of preparing mobile classes and encourage teachers to try this form of work.
Keywords: edukacja mobilna; socjologia i społeczeństwo; materiały dla nauczycieli